Consensus numbering system for the rifampicin resistance-associated rpoB gene mutations in pathogenic mycobacteria. (March 2017) - Andre, E.; Goeminne, L.; Cabibbe, A.; Beckert, P.; Kabamba Mukadi, B.; Mathys, V.; Gagneux, S.; Niemann, S.; Van Ingen, J.; Cambau, E.
Abstract: The rpoB gene codes for the RNA polymerase β subunit, which is the target of rifampicin, an essential drug in the treatment of tuberculosis and other mycobacterial infections. This gene is present in all bacteria, but its length and nucleotide sequence vary between bacterial species, including mycobacteria. Mutations in the rpoB gene alter the structure of this protein and cause drug resistance. To describe the resistance-associated mutations, the scientific and medical communities have been using, since 1993, a numbering system based on the Escherichia coli sequence annotation. Using E. coli reference for describing mutations in mycobacteria leads to misunderstandings, particularly with the increasing use of whole genome sequencing, which brought an alternative numbering system based on the Mycobacterium tuberculosis rpoB sequence. We propose using a consensus numbering system for the reporting of resistance mutations based on the reference genomes from the species interrogated (such as strain H37Rv for M. tuberculosis ). This manuscript provides the necessary figures and tables allowing researchers, microbiologists and clinicians to easily convert other annotation systems into one common language.